Tuesday

January 27, 2015

January 27, 2015

Posted by **Alec** on Monday, January 26, 2009 at 8:51pm.

- algebra -
**Reiny**, Monday, January 26, 2009 at 8:59pmnot quite,

multiply each term by x^2-4, realizing that x^2-4 = (x+2)(x-2)

so you would get

(x-4)(x-2) + 2(x+2) = 17

x^2 - 6x + 8 + 2x + 4 = 17

x^2 -4x - 5 = 0

(x-5)(x+1) = 0

x = 5 or x = -1

**Answer this Question**

**Related Questions**

math,algebra,help - Is this right: Solve: x^2+16x+60=0 this is what i did: i ...

Algebra 2 - Well I'm curently taking this class as a sophmore and have taken ...

algebra 2 - factor 2x^3+54 I factored it to 2(x^3+27). can it be factored more ...

Algebra - How can you factor? 1. x^4 - 4x^2 + 3 2. x^3 - 2x^2 - 4x + 8 Thanks 1...

Algebra II - 1)What method(s) would you choose to solve the equation: x2 + 2x - ...

Algebra - F) Why is (3x + 5) (x - 2) + (2x - 3) (x - 2) not in factored form? ...

algebra - can yu help me solve my algebra problems jiskha/ I use to get help ...

algebra - can yu help me solve my algebra problems jiskha/ I use to get help ...

Algebra - I have to figure out how x^3+216=0 is factored, and what potential ...

Algebra 2 help - What is the expression in factored form? 2x2 + 16x + 24 What is...